Energy harvesting for self-powered systems - Nundrakwang, Songmoung; Yingyong, Phonexai; Isarakorn, Don (My University, 2020)
Harvesting energy from waste energy sources in ambient environmental is the accessible technology in the field of self-power electronic devices for high-efficiency energy due to the power consumption of modern electronic devices that are rapidly developed to microwatt, low-cost, lightweight, and small size. Since numerous research are investigated the technique for converting the ambient energy into useable electrical energy for practical application. Including light, thermal gradients, vibration or motion, and radio-frequency electromagnetic radiation, various forms of waste energy sources are proposed in this review. Their existing power density in the ambient environment is demonstrated. Moreover, the fundamental theory and the application of the energy harvesting devices are discussed as a foundation of the energy conversion technology for self-power electronic devices such as handheld, wearable, and portable devices.
Keywords: Energy conversion; Energy harvesting; Self-powered system; Transducer